Penerapan Terapi Foot Massage Untuk Mengurangi Nyeri pada Pasien Post Sectio Caesarea di RS PKU Muhammadiyah Karanganyar - Anastasia Puri Damayanti; Anjar Nurrohmah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
In the post sectio caesarea (SC) action, it will give an effect, namely the effect of the sensation of pain. Various techniques and methods in nursing care are always developed so that they can be used in providing independent nursing care. Pain control management is a combination of independent nursing interventions with non – pharmacological therapeutic actions, foot massage is a complementary therapy that is safe and easy to give and has the effect of increasing circulation, reducing pain, relaxing muscles and providing comfort to the patient. To describe the description of nursing care by giving foot massage therapy  to post sectio caesarea mothers with pain in RS PKU Muhammadiyah Karanganyar. The design of this study using a descriptive method, was carried out on 2 clients of post sectio caesarea using foot massage which was intervened at 24 hours and 48 hours post sectio caesarea with a frequency of 1x a day, duration of 20 minutes with division every 10 minutes on each extremity. Knowing the description of nursing care by giving foot therapy to post sectio caesarea mothers with pain in RS PKU Muhammadiyah Karanganyar.